The Effect of Curriculum Supervision on School Effectiveness: The Case of Some Selected Public Nursery and Primary Schools in Fako Division, South West Region of Cameroon - Dr. Lingondo Joseph Mwambo; Fonkeng George Epah (International Journal on Integrated Education, 2022)
The focus of this study was on “Curriculum supervision and school effectiveness in public nursery and primary schools in Fako division, South West Region of Cameroon. The objective of this study was to analyze the relationship between curriculum supervision and school effectiveness in public primary schools. The survey research design was adopted for the study. Data was collected from 406 teachers and 62 head teachers from both nursery and primary schools and the number of accessible nursery and primary schools were 23. Questionnaire and semi-structured interview guide were the instruments used for the study. The instruments consisted of both close and open ended questions. Results showed that there is a very significant, positive and moderate relationship between supervision of curriculum and school effectiveness (P=0.000, far less than 0.05). This led to the conclusion that schools are more likely to be effective when supervisory practices (pedagogic, administrative, instructional and curriculum) supervision are carried out effectively. It was recommended that educational state holders from the ministry of basic education should constantly carry out monitoring and supervision at the beginning of the school year and during the various semester of the school year for effective teaching and learning to be enacted.